2017
DOI: 10.1111/jcmm.13446
|View full text |Cite
|
Sign up to set email alerts
|

FHL2 promotes tubular epithelial‐to‐mesenchymal transition through modulating β‐catenin signalling

Abstract: Abstractβ‐Catenin signalling plays an important role in regulating tubular epithelial‐to‐mesenchymal transition (EMT), an indispensable programme for driving renal fibrosis. As an adapter protein, four and a half LIM domain protein 2 (FHL2) acts as a coregulator of β‐catenin in several other cell types. To determine whether FHL2 affects β‐catenin signalling and thus is involved in tubular EMT, we examined its expression and function in the process of TGF‐β1‐induced EMT. FHL2 mRNA and protein were induced by TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…β-Catenin signaling plays an important role in regulating fibrogenic activation. Cai et al reported that overexpression of the adapter protein FHL2 increased β-catenin dephosphorylation, nuclear translocation, and β-catenin-mediated transcription of snail and vimentin (34). AKT can activate β-catenin/TCF transcriptional activity by the indirect stabilization of β-catenin through GSK-3β inhibition and by the direct phosphorylation of β-catenin (35).…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin signaling plays an important role in regulating fibrogenic activation. Cai et al reported that overexpression of the adapter protein FHL2 increased β-catenin dephosphorylation, nuclear translocation, and β-catenin-mediated transcription of snail and vimentin (34). AKT can activate β-catenin/TCF transcriptional activity by the indirect stabilization of β-catenin through GSK-3β inhibition and by the direct phosphorylation of β-catenin (35).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, blockage of Wnt signaling by XAV-939 attenuated the tumor-suppressive effect of FXR knockdown on colon cancer cells. Activation of Wnt/β-catenin signaling is a strong inducer of EMT, as evidenced by the identification of β-catenin-regulated genes, such as fibronectin 48 , slug 15 , MMP-7 49 , and VEGF 50 . These genes, directly or indirectly involved in EMT, code for direct effectors of CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, Fhl2 plays an important role as an essential regulator of stem cell behavior during stress and or inflammation, and in wound-repair processes. In hematopoietic stem cells under regenerative stress (Hou et al, 2014), mesenchymal stem cells during skin wound healing Park et al, 2008), during epithelial-mesenchymal transition (Zhang et al, 2010;Cai et al, 2018), chronic inflammatory arthritis (Wixler et al, 2015) or liver regeneration (Dahan et al, 2013), Fhl2-deficient stem cells show diverse phenotypes. These include reduced self-renewal capacity and migration deficiency, and Fhl2-deficient tissue revealed delayed wound healing, or abnormal inflammatory signal processing and matrix organization during repair (this study; Wixler et al, 2007;Park et al, 2008;Leite Dantas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%